Elements surrounding the ethics committees that hinder their deliberative reasoning - Mondragón Barrios, Liliana (Acta Bioethica, 2013)
Ethics committees are among the most visible manifestations of bioethics. The acceptance these instances have received in recent years has been extensive, but little can be said about their roles and goals, mainly because the analysis of what happens inside the committees has been lagged behind. The aim of this paper is to analyze the elements involved in the inner processes of ethical committees, which are complicating their deliberative reasoning. Elements such as the absence of deliberation from ethical knowledge, the tension between the ethical and legal frameworks, the particularities of the health care field within ethical discernment and the consideration of committees as groups should be permanently and critically recognized and discussed, as self-regulatory work by committees, in order to achieve social and institutional consensus.